2017
DOI: 10.1016/j.ydbio.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-oocyte contact induces outside-in signaling via PYK2 activation

Abstract: Fertilization is a multi-step process that begins with plasma membrane interactions that enable sperm - oocyte binding followed by fusion of the sperm and oocyte plasma membranes. Once membrane fusion has occurred, sperm incorporation involves actin remodeling events within the oocyte cortex that allow the sperm head to penetrate the cortical actin layer and gain access to the ooplasm. Despite the significance for reproduction, the control mechanisms involved in gamete binding, fusion, and sperm incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…[33] PYK2 plays an important role in sexual function such as sperm incorporation by being recruited to the oocyte cortex, incorporating the sperm head via actin and responding to sperm binding. [34] Allingham MJ et al . investigated the function of tyrosine phosphorylation in the mediation of junctions during leukocyte transendothelial migration and found that ICAM-1 is involved in the mediation of SRC- and PYK2-dependent vascular endothelial cadherin tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…[33] PYK2 plays an important role in sexual function such as sperm incorporation by being recruited to the oocyte cortex, incorporating the sperm head via actin and responding to sperm binding. [34] Allingham MJ et al . investigated the function of tyrosine phosphorylation in the mediation of junctions during leukocyte transendothelial migration and found that ICAM-1 is involved in the mediation of SRC- and PYK2-dependent vascular endothelial cadherin tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In females, it has also been reported to be localized to microtubule organizing center or concentrated in cortical cytoskeleton of the oocytes, and played important roles in spindle assembly (Meng et al, 2018) or oocyte maturation (Meng et al, 2006). Moreover, some other studies also found that Ptk2b functioned during fertilization (McGinnis, Luo, & Kinsey, 2013; Meng et al, 2016) and the Ptk2b disruption prevented the incorporation of sperm to the ooplasm (Luo, McGinnis, Carlton, Beggs, & Kinsey, 2014; Wang, Luo, Carlton, McGinnis, & Kinsey, 2017). However, all the studies above were performed in vitro, in vivo validation of its exact reproductive relative biological functions, especially in folliculogenesis is still missing.…”
Section: Introductionmentioning
confidence: 93%
“…Ptk2b disruption prevented the incorporation of sperm to the ooplasm (Luo, McGinnis, Carlton, Beggs, & Kinsey, 2014;Wang, Luo, Carlton, McGinnis, & Kinsey, 2017). However, all the studies above were performed in vitro, in vivo validation of its exact reproductive relative biological functions, especially in folliculogenesis is still missing.…”
Section: And Thementioning
confidence: 99%
“…In mammals, it is now known that the "fusion hypothesis" describes how egg activation occurs—sperm−egg fusion precedes and is required for egg activation, and leads to the release of PLCζ from the sperm into the egg cytoplasm (Hachem et al, 2017; Lawrence, Whitaker, & Swann, 1997). Although PLCζ‐initiated calcium transients appear to be the key trigger for nearly all egg activation responses, recent data suggest that sperm−egg adhesion can induce some cellular changes in the egg, including localized remodeling of actin in the egg cortex (Wang, Luo, Carlton, McGinnis, & Kinsey, 2017). The egg actomyosin cytoskeleton is a potential mediator of the membrane block, based on data from mice (Mackenzie et al, 2016; McAvey et al, 2002), and similarly, the surf clam Spisula has a persistent membrane block (in addition to a transient electrical block) that is impaired by actin perturbation and is not mediated by cortical granule exocytosis (Longo, 1976; Ziomek & Epel, 1975).…”
Section: The Membrane Block Polyspermy In Mammalian Eggsmentioning
confidence: 99%